Family matters in Canada: understanding and addressing family homelessness in Ontario - Cheryl Forchuk; Gordon Russell; Jan Richardson; Chantele Perreault; Heba Hassan; Bryanna Lucyk; Sebastian Gyamfi (BMC, 2022)
Abstract Background Homelessness is becoming an international public health issue in most developed countries, including Canada. Homelessness is regarded as both political and socioeconomic problems warranting broad and consistent result-oriented approaches. Methods This paper represents the qualitative findings of a project that explored risk factors associated with family homelessness and strategies that could mitigate and prevent homelessness among families using a focused ethnographic study guided by the principles of participatory action research (PAR). The sample includes 36 family members residing at a family shelter who participated in focus groups over two years (between April 2016 and December 2017). Most of the participants were single-parent women. Results The analysis yielded five major themes including, life challenges, lack of understanding of the system, existing power differentials, escaping from hardship, and a theme of proposed solutions for reducing family homelessness in the community. Conclusion The findings illustrated the complex nature of family homelessness in Ontario; that the interaction of multiple systems can put families at risk of homelessness. Findings from this study underscore the need for urgent housing protocols aimed at educating homeless families on how to navigate and understand the system, enhance their conflict resolution skills, and develop strategies beyond relocation to help them to cope with difficulties with housing.